2021
DOI: 10.1155/2021/3819900
|View full text |Cite
|
Sign up to set email alerts
|

Block Matching Pyramid Algorithm-Based Analysis on Efficacy of Shexiang Baoxin Pills Guided by Echocardiogram (ECG) on Patients with Angina Pectoris in Coronary Heart Disease

Abstract: This paper was aimed to explore the application of the block matching pyramid (BMP) algorithm in echocardiographic spot tracking in patients with coronary heart disease (CHD) and angina pectoris, as well as the effect of Shexiang Baoxin pills (a kind of drug containing musk, which is good for cardiac diseases) on blood lipids, cardiac function, and curative effect. 206 patients with CHD angina pectoris in the hospital from July 2018 to May 2020 were selected as the research subjects and were enrolled into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…These findings suggest that ET intervention has a positive impact on improving the cardiac and pulmonary function of patients. Consistent with related research, long-term aerobic exercise has been shown to significantly enhance cardiopulmonary function and exercise endurance in cardiovascular disease patients after PCI [ 21 ]. Moreover, long-term aerobic exercise can improve the morphological and structural aspects of the cardiovascular system, enhancing physiological adaptability [ 22 ].…”
Section: Discussionsupporting
confidence: 74%
“…These findings suggest that ET intervention has a positive impact on improving the cardiac and pulmonary function of patients. Consistent with related research, long-term aerobic exercise has been shown to significantly enhance cardiopulmonary function and exercise endurance in cardiovascular disease patients after PCI [ 21 ]. Moreover, long-term aerobic exercise can improve the morphological and structural aspects of the cardiovascular system, enhancing physiological adaptability [ 22 ].…”
Section: Discussionsupporting
confidence: 74%
“…Markedly effective (ME): The electrocardiogram result was normal and the frequency of angina pectoris per week was 1 /5 of that before treatment; Effective (E): The electrocardiogram result was normal and the frequency of angina pectoris per week was 1 /5 -1 /2 of that before treatment; Ineffective: The electrocardiogram result was not improved or aggravated as compared with those before treatment [8]. Overall response rate (R) was calculated using Eq 1.…”
Section: Criteria For Efficacy Evaluationmentioning
confidence: 99%
“…Long-term historical experiences show that the cooperation of TCM and western medicine may be more efficient for the cure and prevention of disease than each of them separately. Numerous studies reported the potential benefits of combined TCM and western medicine in improving tumor prognosis, reducing adverse reactions, and enhancing life quality (8)(9)(10)(11)(12). Recent clinical evidence indicates that the cooperation of Chinese patent medicines (CPMs) and DEX had a good effect on lowing cardiotoxicity and improving the anti-tumor efficiency of anthracyclines (13).…”
Section: Introductionmentioning
confidence: 99%